Case Report: Disappearance of Coronary Anastomotic Aneurysm by Steroid Therapy in Takayasu Arteritis: Pseudorepair of Pseudoaneurysm? - Naraoka, Shuichi; Uchiyama, Hiroki; Yano, Toshiyuki; Mikami, Takuma; Harada, Ryo; Kuroda, Yosuke; Toda, Yuki; Muranaka, Atsuko; Sugawara, Taro; Hasegawa, Tadashi; Miura, Tetsuji; Kawaharada, Nobuyoshi (Frontiers in Cardiovascular Medicine, 2021)
Background: Takayasu arteritis (TA) is a large vessel vasculitis of unknown etiology characterized by chronic inflammatory changes of the aorta and its major branches. Complications such as anastomotic aneurysm and valve detachment have been reported in active TA patients who received aortic valve replacement and graft replacement of aorta. Case Summary:A 61-year-old man with a history of emergency aortic valve replacement and patch closure of the noncoronary sinus of Valsalva due to acute heart failure induced by acute aortic regurgitation and ruptured sinus of Valsalva 4 years ago was referred for exertional dyspnea. Dilatation of the sinus of Valsalva together with protrusion of the right sinus of Valsalva and ostial stenosis of the left coronary artery were newly found by computed tomography (CT). A Bentall operation with concomitant coronary artery bypass grafting was successfully performed with a composite graft. Diagnosis of TA was made on the basis of histological analyses of the resected sinus of Valsalva, though other arterial manifestations were not detected by 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography. Three months later, a follow-up study revealed left coronary ostial pseudoaneurysm at the anastomotic site together with strong 18F-FDG uptake, leading to commencement of steroid therapy. Eight months later, disappearance of left coronary ostial pseudoaneurysm was found by a follow-up CT scan. Conclusion: This is a rare TA case in whom spontaneous resolution of coronary anastomotic aneurysm by steroid therapy was found without reconstructive surgery.